The Gothic Bible studies in 20th century USA. Status and results - Christian T. Petersen (Filologia Germanica, 2025)
As a matter of course, science has to keep up with the findings. Only generations later, some papers have caused laughter in hindsight. Nonetheless, scholars had to dare to make the best out of their sources. Whilst editions of the Codex Argenteus became even more elaborate by comments and translations, mere grammar and vocabulary studies came into existence. The ‘Neuzeit’ output is connected to names as Grimm and many others. Especially in the past century, publications on Gothic have proliferated, and some text books still found their way to college and university – be it in Europe or America: especially US immigrants with German background have deserved their credits. Nowadays, Bologna-process, PISA-studies and the like have rung the death knell for this very discipline. Sapere aude!